Neurologic considerations for adolescent athletes - Patel, D. R.; Greydanus, D. E. (Adolescent Medicine, 2002)
Sports-related head injuries in young athletes can have both acute and long-term complications. Concussions are the most common type of diffuse brain injury in young athletes. Research on concussions in young athletes is limited. Most current management guidelines are based on expert opinion and consensus. The role neuropsychological testing as an objective measure is increasingly being recognized in the management of concussions. This article reviews practical aspects of concussion management. The implications for sport participation by athletes with epilepsy, sport-related headaches, and burner syndrome are also reviewed.